Дослідження систем Pr2X3–Cu2X–ZX2 (Z=Si, Ge; X=S, Se) при 870 K - Личманюк, Ольга Сергіївна; Гулай, Любомир Дмитрович; Олексеюк, Іван Дмитрович; Lychmanyuk, O. S.; Hulai, Liubomyr D.; Olekseiuk, Ivan D. (Волинський державний університет імені Лесі Українки, 2007)
Ізотермічні перетини систем Pr2X3–Cu2X–ZX2 (Z=Si, Ge; X=S, Se) при 870 K побудовано за результатами рентгенофазового аналізу. Підтверджено існування тернарних сполук на обмежуючих сторонах та тетрарних сполук R3CuZX7. The isothermal sections of the Pr2X3–Cu2X–ZX2 (Z=Si, Ge; X=S, Se) systems at 870 K were investigated using X-ray powder diffraction. The existence of ternary compounds on the bound sides was confirmed. The existence of quaternary R3CuZX7 compounds was confirmed in the investigated systems.
Investigation of the Pr2X3–Cu2X–ZX2 (Z=Si, Ge; X=S, Se) Systems at 870 K.
Keywords: халькогеніди; сполуки РЗМ; сполуки Cu; сполуки Si; сполуки Ge; сполуки S; сполуки Se; ізотермічний перетин; рентгенівський метод порошку; chalcogenides; rare earth compounds; Cu compounds; Si compounds; Ge compounds; S compounds; Se compounds; isothermal section; X-ray powder diffraction